Entrepreneurial competency, resilience, and financial literacy: Drivers of sustainable performance in SMEs for societal welfare - Flores, Gladys; Maravilla Jr., Vicente S. (Journal of Sustainability, Society, and Eco-Welfare, 2025)
Background: Small and medium enterprises (SMEs) are crucial to the Philippine economy, contributing significantly to employment and GDP. However, challenges such as natural disasters (e.g., Typhoon Haiyan), economic disruptions, and limited financial resources have tested the resilience of entrepreneurs, especially in Tacloban City, Leyte. This study explores the interplay between financial literacy, entrepreneurial competency, and resilience and their combined impact on the sustainable performance of SMEs in Tacloban City. Methods: A descriptive-correlational research design was utilized, employing a structured questionnaire adapted from existing validated tools. Data were collected from 224 respondents across service, retail, and insurance sectors, selected through cluster sampling. Relationships among financial literacy, entrepreneurial competency, resilience, and sustainable performance were analyzed using SmartPLS-SEM. The mediating role of resilience was also assessed. Findings: The results indicate that financial literacy significantly enhances entrepreneurial competencies and resilience, both of which positively influence the sustainable performance of SMEs. Entrepreneurial resilience partially mediates the relationship between entrepreneurial competency and sustainable performance, highlighting its critical role in overcoming challenges. Demographic factors, such as age and education, were found to influence perceptions of sustainable performance. Conclusions: The findings underscore the importance of financial literacy as a foundational element in fostering entrepreneurial competency and resilience. Tailored interventions, such as financial education programs and resilience-building workshops, are recommended to support SME sustainability, particularly in disaster-prone regions like Tacloban City. Novelty/Originality: This study extends existing research by applying a resilience mediation model to a unique geographic and socio-economic context, Tacloban City, known for its vulnerability to natural disasters. The inclusion of demographic variables adds depth to the understanding of resilience and sustainability among SMEs in this setting, providing actionable insights for policymakers and stakeholders.